Considerations for ensuring safety and efficacy of vaccines and therapeutic proteins manufactured by using platform approaches : summary of a workshop - Fox, Jeffrey (Jeffrey L.); Shelton-Davenport, Marilee; Hook-Barnard, India (National Academies Press, 2010)
On September 15, 2008, the National Academies held the workshop "Considerations for Ensuring Safety and Efficacy of Vaccines and Therapeutic Proteins Manufactured by Using Platform Approaches". The workshop was planned and organized by an ad hoc planning committee made up of members of the Standing Committee on Biodefense at the US Department of Defense. The charge to the planning committee was to bring together scientists from academe, government, and the biotechnology industry to identify and discuss challenges and ideas related to the Transformational Medical Technologies Initiative's (TMTI) vision of developing countermeasures within a few months after a biologic-warfare agent is identified. The workshop focused on manufacturing processes and specifically on the development of "manufacturing platforms"--Repeatable components of manufacturing that reduce both development time and risk. An underlying assumption was that demonstrating that integrated platforms can reliably produce safe and efficacious countermeasures might shorten the regulatory approval process. Participants discussed manufacturing-related characteristics of monoclonal antibodies and vaccines. Although the planning committee understood that the TMTI efforts are broader than biologics and that TMTI platform approaches for biologics extend beyond monoclonal antibodies and vaccines, the planning committee believed that focusing on monoclonal antibodies and vaccines could illustrate some of the promise and challenges of platform approaches